PEGylated Biopharmaceuticals: Current Experience and Considerations for Nonclinical Development. (October 2015) - Ivens, Inge A.; Achanzar, William; Baumann, Andreas; Brändli-Baiocco, Annamaria; Cavagnaro, Joy; Dempster, Maggie; Depelchin, B. Olympe; Irizarry Rovira, Armando R.; Dill-Morton, Laura; Lane, Joan H.; Reipert, Birgit M.; Salcedo, Theodora; et al.
PEGylation (the covalent binding of one or more polyethylene glycol molecules to another molecule) is a technology frequently used to improve the half-life and other pharmaceutical or pharmacological properties of proteins, peptides, and aptamers. To date, 11 PEGylated biopharmaceuticals have been approved and there is indication that many more are in nonclinical or clinical development. Adverse effects seen with those in toxicology studies are mostly related to the active part of the drug molecule and not to polyethylene glycol (PEG). In 5 of the 11 approved and 10 of the 17 PEGylated biopharmaceuticals in a 2013 industry survey presented here, cellular vacuolation is histologically observed in toxicology studies in certain organs and tissues. No other effects attributed to PEG alone have been reported. Importantly, vacuolation, which occurs mainly in phagocytes, has not been linked with changes in organ function in these toxicology studies. This article was authored through collaborative efforts of industry toxicologists/nonclinical scientists to address the nonclinical safety of large PEG molecules (>10 kilo Dalton) in PEGylated biopharmaceuticals. The impact of the PEG molecule on overall nonclinical safety assessments of PEGylated biopharmaceuticals is discussed, and toxicological information from a 2013 industry survey on PEGylated biopharmaceuticals under development is summarized. Results will contribute to the database of toxicological information publicly available for PEG and PEGylated biopharmaceuticals.